Case Report: Visual Deprivation in Pusher Syndrome Complicated by Hemispatial Neglect After Basal Ganglia Stroke - Zhang, Qian; Zhang, Lixia; He, Wei; Zheng, Xuemei; Zhao, Zhengrui; Li, Yuanli; Xu, Shutian; Zheng, Juan; Zhuang, Xin; Jia, Wenting; Zhu, Chengyuan; Xu, Hua; et al. (Frontiers in Neurology, 2021)
We aimed to explore whether motor function and activities of daily life (ADL) could be improved with the application of visual deprivation in two patients with Pusher syndrome complicated by hemispatial neglect after right basal ganglia stroke. We assessed two stroke patients suffering from severe motor disturbances, both tilting heavily to the left, with diagnoses of Pusher syndrome and left hemispatial neglect. Vision in the left eye was deprived using patches during clinical rehabilitation. Motor function promotion was confirmed using the Burke Lateropulsion Scale (BLS), Fugl-Meyer Balance Scale (FMBS), and Holden grade (HG), while the Barthel index (BI) was applied to assess ADL immediately and 1 week after intervention. Both patients regained standing balance immediately using visual deprivation, as well as walking ability, although both scored 0 on the FMBS and HG. After 1 week of treatment, one increased to 11 on FMBS and 3 on HG, while the BLS score decreased from 12 to 2, and the ADL increased from 23 to 70. The other patient demonstrated increases to 10 on FMBS and 3 on HG with the BLS decreasing from 13 to 3, and the ADL increasing from 25 to 60. In the rehabilitation treatment of Pusher syndrome complicated by hemispatial neglect due to basal ganglia stroke, visual deprivation can improve motor function significantly and shorten the treatment course.